Abstraction, reformulation, and approximation : [electronic resources] 7th international symposium, SARA 2007, Whistler, Canada, July 18-21, 2007 : proceedings - SARA 2007 (2007 : Whistler, B.C.); Miguel, Ian; Ruml, Wheeler; SpringerLink (Online service) (Berlin ; New York : Springer)
41